Domestic Demand and Export Performance in CEMAC: An Assessment with Endogeneity-related Model - Oscar Kuikeu (Universitas Negeri Malang, 2024)
Based on several alternative approaches there is by now some evidence suggesting that there is a negative relationship between exports and domestic sales. But in the majority of cases this regularity has focused on industrialized countries. While the external trade of African countries faces numerous challenges, with the low level of intra regional trade and the concentration of exports in some raw materials. Thus the aim of this paper to assess this new export channel for African countries. We then estimate a dynamic panel model with an error correction mechanism of the export market share (the difference between exports and foreign demand) for the six economies of the CEMAC zone between 1974 and 2021. Through the use of instrumental variables (2SLS) we address the role of endogeneity. According to the results, such link is prominent for African countries such the CEMAC countries where domestic demand impacts effectively negatively exports in CEMAC with a negative elasticity of around 53 %. When allowing for an asymmetric relationship between domestic sales and exports the results remain unchanged suggesting that a significant relationship between domestic demand and exports performance still holds.